Quantification of postural control deficits in patients with recent concussion: An inertial-sensor based approach. (February 2017) - Doherty, Cailbhe; Zhao, Liang; Ryan, John; Komaba, Yusuke; Inomata, Akihiro; Caulfield, Brian
Abstract: Background: The aim of this study was to quantify postural control ability in a group with concussion compared with a healthy control group. Method: Fifteen concussion patients (4 females, 11 males) and a group of fifteen age- and sex-matched controls were recruited. Participants were tested during the performance of the three stance variants (bilateral, tandem and unilateral) of the balance error scoring system standing on a force place, while wearing an inertial measurement unit placed at the posterior aspect of the sacrum. Findings: The area of postural sway was computed using the force-plate and the '95% ellipsoid volume of sway' was computed from the accelerometer data. Concussed patients exhibited increased sway area (1513 mm 2 [95% CI: 935 to 2091 mm 2 ] vs 646 mm 2 [95% CI: 519 to 772 mm 2 ]; p = 0.02) and sway volume (9.46 m 3 s − 6 [95% CI: 8.02 to 19.94 m 3 s − 6 ] vs 2.68 m 3 s − 6 [95% CI: 1.81 to 3.55 m 3 s − 6 ]; p = 0.01) in the bilateral stance position of the balance error scoring system. The sway volume metric also had excellent accuracy in identifying task 'errors' (tandem stance: 91% accuracy [95% CI: 85–96%], p < 0.001; unilateral stance: 91% accuracy [95% CI: 86–96%], p < 0.001). Interpretation: Individuals with concussion display increased postural sway during bilateral stance. The sway volume that was calculated from the accelerometer data not only differentiated a group with concussion from a healthy control group, but successfully identified when task errors had occurred. This may be of value in the development of a pitch-side assessment system for concussion. Highlights: Postural control performance is evaluated in a cohort with recent concussion. Traditional and novel technologies were used to measure performance. Postural 'sway' was quantified with a force plate and a wearable sensor. Concussed patients exhibit increased sway in bilateral stance. These alterations are likely reflective of impaired sensorimotor control.